Use of the virtual laboratory and learning achievements transcription and translation of the genetic code - Carhuaricra Meza, Julio C. (2024)
The research records the level of relationship between the use of virtual laboratories and the learning achievements of the transcription and translation processes of the genetic code based on the molecular model of protein synthesis (mmsp) in the teacher training program specialized in biology and chemistry from the Daniel Alcides Carrión National University. Pasco, Perú. Regarding the methods, techniques and instruments, the deductive hypothetical was applied for the conceptual theoretical treatment and then the inductive one, which was based on the learning achieved in the virtual molecular biology laboratory of the University of Alcalá de Henares in Spain. Subsequently, it was ascended until reaching the corresponding generalization. For this process, successive triangulation has been used that considered the sources of data and statistical and documentary information. Everything was centralized in a focus group made up of 10 students from the V semester who took the subject of cytology and genetics as part of the curriculum of the announced program. In conclusion, it has been shown that the use of the laboratory is related to the achievements of cognitive learning, procedural inquiry, technological and academic integrity, all aligned with the processes of transcription and translation of genetic codes.